1994
DOI: 10.1029/94wr00154
|View full text |Cite
|
Sign up to set email alerts
|

Flood frequency analysis with systematic and historical or paleoflood data based on the two‐parameter general extreme value models

Abstract: Historical and paleoflood data have become an important source of information for flood frequency analysis. A number of studies have been proposed in the literature regarding the value of historical and paleoflood information for estimating flood quarttiles. These studies have been generally based on computer simulation experiments. In this paper the value of using systematic and historical/paleoflood data relative to using systematic records alone is examined analytically by comparing the asymptotic variances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
0
12

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(101 citation statements)
references
References 21 publications
3
86
0
12
Order By: Relevance
“…1). Generally, this minimum flood level required to assure documentary evidence of flooding is related with a perception threshold to which the contemporary society was susceptible in terms of damage or social disruption (Stedinger and Cohn, 1986;Francés et al, 1994). This perception threshold is frequently related to a flood water level within urban zones and build-ings with distinct characteristics (e.g.…”
Section: Flood Frequency Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…1). Generally, this minimum flood level required to assure documentary evidence of flooding is related with a perception threshold to which the contemporary society was susceptible in terms of damage or social disruption (Stedinger and Cohn, 1986;Francés et al, 1994). This perception threshold is frequently related to a flood water level within urban zones and build-ings with distinct characteristics (e.g.…”
Section: Flood Frequency Analysismentioning
confidence: 99%
“…For instance, flooding of the Aranjuez Royal gardens (Spain) is produced when the River Tagus overtopped the river banks during discharges exceeding 300 m 3 s −1 (Benito et al, 2003a). A list of k i observations above an arbitrary specified discharge threshold X i in n i years is similar to the analysis of partial duration series (data censored above threshold; Stedinger and Cohn, 1986;Francés et al, 1994;Francés, 2001). Statistically it is important to confirm that years with lack of a historical flood record really corresponded to flows smaller than the discharge threshold X i .…”
Section: Flood Frequency Analysismentioning
confidence: 99%
“…with the rarity associated to the target design event), but reaches a minimum at some value of T. In general this minimum is reached when T is such that X 0 corresponds to the Q T quantile, for example T=100 when X 0 corresponds to the 99 th percentile of the distribution, or T=10 when X 0 corresponds to the 90 th percentile. In [14] this property is described by means of the asymptotic variances of GEV parent distributions. Although not proved in a mathematical way, this seems to hold for the simulation study in this paper.…”
Section: Flood Frequency Curves Estimationmentioning
confidence: 99%
“…The stratigraphic record is assumed to be complete for each flood exceeding the threshold of discharge at the palaeoflood site. As such, palaeoflood information can be treated as censored data, which can be handled efficiently by appropriate statistical methods (Stedinger and Cohn, 1986;Francés et al, 1994). Frequency analysis of a 500-yr flood record introduces the question of flood stationarity, since cyclic and systematic climatic and land-use conditions may affect the assumption of statistical parametric models on which the random variable (flood discharge) is independent and identically distributed (see discussion in Redmond et al, 2002;Francés, 2004 The associated FFA curves are shown in Fig.…”
Section: Flood Frequency Analysis (Ffa) Combining Modelled Dischargesmentioning
confidence: 99%